Artificial Intelligence, Healthcare, Clinical Genomics, and Pharmacogenomics Approaches in Precision Medicine - Abdelhalim, Habiba; Berber, Asude; Lodi, Mudassir; Jain, Rihi; Nair, Achuth; Pappu, Anirudh; Patel, Kush; Venkat, Vignesh; Venkatesan, Cynthia; Wable, Raghu; Dinatale, Matthew; Fu, Allyson; et al. (Frontiers in Genetics, 2022)
Precision medicine has greatly aided in improving health outcomes using earlier diagnosis and better prognosis for chronic diseases. It makes use of clinical data associated with the patient as well as their multi-omics/genomic data to reach a conclusion regarding how a physician should proceed with a specific treatment. Compared to the symptom-driven approach in medicine, precision medicine considers the critical fact that all patients do not react to the same treatment or medication in the same way. When considering the intersection of traditionally distinct arenas of medicine, i.e., artificial intelligence, healthcare, clinical-genomics, and pharmacogenomics - what ties them together is their impact on the development of precision medicine as a field, and how they each contribute to patient-specific, rather than symptom-specific patient outcomes. This study discusses the impact and integration of these different fields in the scope of precision medicine and how they can be used in preventing and predicting acute or chronic diseases. Additionally, this study also discusses the advantages as well as the current challenges associated with artificial intelligence, healthcare, clinical-genomics, and pharmacogenomics.